Chimeric T7 bacteriophage particles displaying VP1 epitopes as a diagnostic tool detecting foot-and-mouth disease virus antibodies in bovine serum samples - Wong, Chuan Loo (2019)
Over the past 50 years, growing populations with rising per capita incomes and progressive urbanisation have spurred the rapid growth in the consumption of livestock products, with Asia being the largest meat producer, accounting for 40-45% of total meat production. Cattle are one of the main meat sources for humans, with a yearly revenue of about US$ 2 trillion. Incursion of foot-and-mouth disease virus (FMDV) in cloven-hoofed animals posed a major threat to the cattle industry. Conventionally, ELISAs based on FMDV non-structural proteins (NSPs) were used for serological detection of the viral infection. Nonetheless, one shortcoming of these diagnostic methods is the inability to rule out the heavily persistent infected animals in a vaccinated population, and they cannot be used to determine the animal vaccination status. Therefore, this study aimed to develop a structural protein (SP)-based detection method by displaying FMDV VP1 epitopes on bacteriophage T7. A phage ELISA based upon the recombinant T7-FOVP1131-170 phage displaying residues 131-170 of the VP1 protein was established. The assay was able to detect anti-FMDV antibodies in bovine serum samples up to 94% sensitivity, allowing sufficient discrimination of naïve bovine sera from the infected and vaccinated sera. Based on the amino acid sequence alignment and homology modelling, the functional epitope was further delineated and two highly conserved regions (VP1145-152 and VP1159-170) were identified, fused independently to the T7 genome and displayed on the phage particles. The chimeric T7 phage displaying the VP1159-170 demonstrated a higher antigenicity compared to T7-FOVP1131-170, with 100% and 87.5% assay sensitivity and specificity, respectively. By contrast, T7 phage displaying the VP1145-152 epitope did not react significantly with the anti-FMDV antibodies in vaccinated bovine sera. A T7 phage displaying VP1131-170 was further utilised to develop an on-site diagnostic test strip based on lateral flow immunochromatographic (LFI) system. A LFI strip composed of a sample pad, conjugate pad, and absorbent pad was assembled on a nitrocellulose membrane card. The proof of concept was performed using a test model based on avidin-biotin interaction which resulted in the generation of a strong positive test line. Upon confirming the LFI system, development of LFI strip for detection of anti-FMDV antibodies in bovine serum samples was then conducted. The conjugation of goat anti-bovine antibody to 40 nm colloidal gold particles was analysed for surface plasmon resonance (SPR) and hydrodynamic size using ultraviolet-visible (UV-vis) spectroscopy and dynamic light scattering (DLS) machine, respectively. Concomitant with the increase in SPR, the diameter of gold nanoparticle was also increased by approximately 0.3-9.6 nm. The optimal amount of anti-bovine antibody conjugated to 500 μl of gold solution on the assembled LFI strips was 1 ng, pre-coated with T7-FOVP1131-170 phage with FMDV vaccinated bovine serum as the test analyte. Semi-quantitation of the average pixel intensity performed using the MatLab® image analysis code has revealed a high saturation (S) value for 1 ng of antibody. To further improve the sensitivity of the LFI strips, sucrose was included in the conjugate solution to facilitate the release of the gold conjugate from the conjugate pad, where 10% (w/v) of sucrose has resulted in a positive test line with the highest S value. Lastly, dilution factor of the test analyte was optimised, where 5,000-fold dilution of the vaccinated bovine serum has resulted in a positive test line with the highest S value. Both the naïve and FMDV-vaccinated bovine serum samples were used to validate the developed LFI strips after the parameters were optimised. Nevertheless, both the vaccinated and naïve serum samples showed indifferent positive test results. The naïve serum sample was later found to generate a positive test line when wild-type T7 phage was dotted on the signal generation membrane as the coating antigen instead of T7-FOVP1131-170 phage, suggesting the presence of anti-T7 antibodies in bovine serum samples. Therefore, this study concluded that T7 phage is not a suitable carrier to be used for the development of LFI assay for detecting anti-FMDV antibodies in serum samples.